Pemeriksaan Kesehatan Dan Home Program Pada Kondisi Carpal Tunnel Syndrome Di Tlogosari Wetan, Semarang Timur - Syurrahmi Syurrahmi; Purna Luberto; Dana Faricha; Mutiara Andriyani; Eriga Yessyra Syafitri (SAFARI :Jurnal Pengabdian Masyarakat Indonesia, 2022)
Carpal Tunnel Syndrome is a disorder that occurs when the median nerve is compressed, which is the nerve that controls the sense of feeling and movement in the wrist and hand. This problem arises when the median nerve, which controls the sense of feeling and movement in the wrist and hand, is compressed. The nerve passes through a structure in the wrist that takes the form of a median nerve tunnel that shrinks and moves towards the wrist. Typically, carpal tunnel syndrome gets worse over time. At a mild level, symptoms of carpal tunnel syndrome can be relieved by using a wrist splint, or avoiding certain activities in the first place.If the pressure on the median nerve continues, the nerve will eventually be damaged and symptoms will worsen. To prevent this from happening, patients may have to undergo surgery to relieve pressure on the median nerve. Carpal Tunnel Syndrome is a condition often experienced by computer users, cashiers, butchers, janitors, and other workers who allow both hands to perform repetitive movements for a long time. Home program is a therapy program that is done at home. This program Home programs can be conducted by parents or parents together with a therapist, as long as they are integrated. Home programs are very diverse and broad, they are not formal. However, they can be more flexible and "homey", learning by playing, learning by talking, and learning by communicating. Although simple, these activities are of great significance for improving functional abilities. The Gasem Wulung Asri community, especially the PKK association, often complains of wrist pain. To prevent Carpal Tunnel Syndrome, it is necessary to provide knowledge about the symptoms, especially the Home program in preventing Carpal Tunnel Syndrome. The output target is the achievement of community empowerment and increased awareness and knowledge about Carpal Tunnel Syndrome, the publication of community service results in national journals, and electronic media.